Arab women writers : a critical reference guide, 1873-1999 - ʻĀshūr, Raḍwá; Ghazoul, Ferial Jabouri, 1939-; Reda-Mekdashi, Hasna; McClure, Mandy (American University in Cairo Press, 2008)
Traces the development of Arab women's literature from the nineteenth-century through the end of the twentieth century. Also includes a comprehensive bibliography of writing by Arab women.